A ingestão elevada de frutose altera a reatividade vascular mesentérica em ratos normotensos - Sousa, Glauciene Januário de (2017)
Chronic metabolic diseases are a common outcome of modern western lifestyle, as shown by the current prevalence of as obesity, insulin resistance and metabolic syndrome (MS), which correlates with increased fructose consumption and can leads to cardiovascular diseases. We hypothesize that high intake of chronic fructose mimics the early stages of cardiometabolic disease like to the MS, leading to initial vascular alterations. Methods: Wistar rats was separated in tow groups: (FRU) fructose 10% in drink water for 6 weeks and (CON) without fructose. Blood pressure was evaluated by tail plethysmography. Fasting glucose, insulin and glucose tolerance test was made using a strip-based glucometer. Mesenteric vascular beds reactivity was tested in a perfused system. Western blot analysis of iNOS, eNOS, Nox2 and COX-2 was performed. DHE stain was used to vascular O2 - detection. Scanning electron microscopy provided ultrastructural vessel observation. Results: Blood pressure was no altered. FRU shown increased visceral fat deposition and liver weight as well as increased fasting glucose and impaired insulin and glucose tolerance. Fructose increased NEinduced vasoconstriction which was abolished by both indomethacin and endothelium removal. ACh-induced relaxation was preserved, and L-NAME promoted a significant reduction in response in the FRU group. The SNP-induced relaxation was not altered. Protein expression of iNOS was increased, however, there was no changes in the eNOS, Nox2 and COX-2. DHE shown no differences. Additionally, the scanning electron microscopy images showed a slight disarray in the endothelium layer surface that are suggestive of derangement of the intima layer with a change in the shape and arrangement of the endothelial cells. Conclusions: High fructose intake for 6 weeks leads to metabolic disturbance and promotes increased NOR-induced vasoconstriction through endothelial prostaglandins pathway as well as increased the NO-mediated relaxation associated with iNOS increase.